2001
DOI: 10.1007/s002130100901
|View full text |Cite
|
Sign up to set email alerts
|

Hypolocomotor effects of acute and daily d-amphetamine in mice lacking the dopamine transporter

Abstract: These findings indicate that partial or total DAT gene deletion result in decreased locomotion in response to d-amphetamine and modify behavioral sensitization depending on the proportion of DAT removed, suggesting that inhibition of the DAT is necessary for the development of sensitization to psychostimulant drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 20 publications
9
69
0
Order By: Relevance
“…This increased responsiveness to amphetamine is in accord with the molecular mechanism of amphetamine action in which its DA-releasing activities are dependent on DAT (9). Indeed, we and others (22)(23)(24) have reported that the DAT heterozygous animals, or animals in which DAT expression has been reduced by 50% via siRNA treatment, demonstrate a commensurate reduction in amphetamine-induced locomotor activation. It thus seems clear that the locomotor-stimulating effects of amphetamine are absolutely dependent and directly proportional to the levels of DAT.…”
Section: Discussionsupporting
confidence: 82%
“…This increased responsiveness to amphetamine is in accord with the molecular mechanism of amphetamine action in which its DA-releasing activities are dependent on DAT (9). Indeed, we and others (22)(23)(24) have reported that the DAT heterozygous animals, or animals in which DAT expression has been reduced by 50% via siRNA treatment, demonstrate a commensurate reduction in amphetamine-induced locomotor activation. It thus seems clear that the locomotor-stimulating effects of amphetamine are absolutely dependent and directly proportional to the levels of DAT.…”
Section: Discussionsupporting
confidence: 82%
“…DAT knockout mice have also been tested for their acute stimulant response to these three drugs. In general WT mice are stimulated by an acute injection of methylphenidate, MDMA, and amphetamine while KO mice are depressed by an acute injection of these drugs Powell et al, 2004;Spielewoy et al, 2001;Zhuang et al, 2001; but see Giros et al, 1996). Therefore, for this trait, the consequence of DAT KO had similar consequences across the three drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple studies examining the acute locomotor response to amphetamine of DAT KO and WT mice, the markedly elevated baseline locomotion of the KO mice likely impacted their ability to exhibit a locomotor stimulant response. In fact, WT mice exhibited the typical activation, whereas KO mice showed locomotor depression , Giros et al, 1996, Spielewoy et al, 2001, Zhuang et al, 2001. The ability of stimulants to reduce the hyperactivity of DAT KO mice has suggested to some that these mice may serve as a model of attention deficit hyperactivity disorder (ADHD).…”
Section: Dopamine-related Genes: Amphetamine and Methamphetaminementioning
confidence: 99%
“…Known strain differences in several other neurochemical systems and in a variety of second messenger proteins (Kosten and Ambrosio 2002) undoubtedly influence these behaviors, as well, but the importance of DATs for AMPH responses in both rodents (e.g., Spielewoy et al 2001) and humans (e.g., Lott et al 2005) has been clearly demonstrated. Indeed, Lott and colleagues (2005) recently identified polymorphisms that affect DAT gene expression as a genetic determinant of differential subjective responsiveness among individuals to AMPH.…”
Section: Discussionmentioning
confidence: 99%